Detection of Bet v1, Bet v2 and Bet v4 specific IgE antibodies in the sera of children and adult patients allergic to birch pollen: evaluation of different IgE reactivity profiles depending on age and local sensitization - Sekerková, A; Poláčková, M (International archives of allergy and immunology, 2011)
BACKGROUND: Birch pollen belongs to the major allergen triggers in the spring season in Europe. Our rapidly expanding knowledge of the allergenic molecules enables us to better recognize the individual differences between the reactivity of specific IgE antibodies of individual patients and allergic populations living in various regions of the world. METHOD: In a group of birch pollen-allergic patients living in the Czech Republic (107 children, 71 adults) we detected the presence of Bet v1, Bet v2 and Bet v4 specific IgE antibodies. RESULTS: Bet v1 specific IgE antibodies were identified in most patients without any significant differences between children and adults. Bet v2 positivity was found more frequently in the group of children than in adults (p = 0.02). In most adult patients Bet v1 monospecificity was more expressed as compared to the pediatric group. More allergic subjects reacted against minor birch allergens in the pediatric group (p = 0.02). Specific IgE antibodies against Bet v1 were not detected in 10% of the tested patients. In this group, 5% of birch pollen-allergic patients were found to not have specific IgE antibodies against any of the tested recombinant allergens. CONCLUSION: The investigation of specific IgE antibodies against Bet v1, Bet v2 and Bet v4 demonstrated that the specificity of allergen-induced IgE antibodies in birch pollen-allergic individuals is dependent not only on the region in which a patient lives but also on age. Especially in children, there is an increase in the number of allergic subjects who do not react exclusively against the major allergen. The question is whether some allergen-specific IgE antibodies will disappear depending on age or on the contrary whether their synthesis will be increased.
Keywords: Young Adult; Male; Child, Preschool; Middle Aged; mladý dospělý; Adolescent; Immunoglobulin E; Infant; Child; Betula; dítě; Adult; Age Factors; Aged; dospělí; bříza; mužské pohlaví; senioři; pyl; Plant Proteins; alergie; mladiství; předškolní dítě; Pollen; lidé; antigeny rostlinné; ženské pohlaví; Humans; Calcium-Binding Proteins; imunoglobulin E; kojenec; věkové faktory; proteiny vázající vápník; Antigens, Plant; Female; Hypersensitivity; lidé středního věku; rostlinné proteiny